Perkembangan Kawasan Terbangun Kota Padang Tahun 1990 - 2020 - Wahyu, Aldo Wahyudi (JURNAL BUANA, 2025)
The development of the city every year will affect the arrangement of the city for the future. The purpose of this research; 1) to determine the development of built-up areas and population growth in the city of Padang from 1990 to 2020, 2) to determine the shape of the development pattern of the city of Padang from 1990 to 2000. The method used in this research is the Normalized Difference Built-up Index and Spatial Metric for knowing the density of buildings and the pattern of the built area of the city of Padang from 1990 to 2020. The results of the study show the development of the built area of the City of Padang from 1990 to 2020, the developments that occur look very significant. The development of the built-up area from 1990 to 2020 has increased by 6937 ha. Judging from the distribution, the development of the built area spreads from the city center to the outskirts of Padang City which shows the direction of the development pattern of the Padang city to sprawl.